THE EFFECTIVENESS OF ACUPRESSURE AT THE LR3, KI3, SP6, ST36, AND SP10 POINT ON ANKLE BRACHIAL INDEX IN PATIENTS WITH DIABETES MELLITUS - Muhammad Anis Taslim; Dhanang Efendi; Madyo Adrianto (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2026)
Background: Type II Diabetes Mellitus (DM) is a chronic metabolic disease that can cause long-term complications, incluiding peripheral artery disease, which can be detected through the Ankle Brachial Index (ABI) examination. Non-pharmacological management, such as acupressure and warm water immersion, serves as a potential complementary therapy to improve ABI scores. Objective: This study determined the difference in ABI values after administering acupressure and warm water immersion therapies to type II DM patients. Method: The researches used a quasi-experimental design with a pretest-posttest approach and two intervention groups: acupressure and warm water immersion. A total of 76 respondents participated. The researches analyzed the data using the paired t-test and independent samples t-test. Results: The paired t-test results showed a significant increase in ABI values after both acupressure (p = 0.001) and warm water immersion (p = 0.000). The independent samples t-test results indicated no significant difference existed between the two. Conclusion: These interventions can serve as alternative non-pharmacological therapies to improve peripheral blood circulation in DM patients.